Causal Modeling of Factors Causing Toddler Stunting Using the Peter-Clark Algorithm - Nurhaeka Tou; Putri Mentari Endraswari; Syafiranur Iftizam (Politeknik Piksi Ganesha Indonesia, 2025)
Stunting is a growth disorder in toddlers that can result in a height that is not proportionate to their age. Between 2016 and 2024, many studies have discussed factors related to stunting. However, these studies generally only use correlation analysis, which indicates the level of closeness of the relationship between variables. Correlation analysis can indeed describe the existence of an association, but cannot explain the causal relationship. Therefore, the causal mechanisms underlying these factors have not been fully revealed. This study aims to model the causal relationship of the factors that cause stunting. This study uses the Peter-Clark algorithm to obtain the direction of the causal relationship. The results of this study show a relationship between Height(TB.U)/Weight(BB.U), Integrated Health Post Visits/Height(TB.U), Height(TB.U)/Mother's Education, Age of Marriage/Mother's Education, Immunization/Family Members Smoking in the Home, and Exclusive Breastfeeding/ Integrated Health Post Visits. The Peter-Clark algorithm in this study successfully identified a causal relationship based on a comparison of performance using directional and causal density of 67%. These results are quite informative, but 34% of the relationships remain undirected. Therefore, additional data, domain assumptions, or advanced algorithms, such as FCI or GES, are needed to determine their direction.